1997
DOI: 10.1063/1.473288
|View full text |Cite
|
Sign up to set email alerts
|

Recombination dynamics of photodissociated I2− in size selected Ar and CO2 clusters

Abstract: We report time-resolved photodissociation and geminate recombination dynamics of I2− in size-selected I2− Arn and I2−(CO2)n cluster ions by using ultrafast pump–probe techniques at 790 nm in conjunction with a tandem time-of-flight mass spectrometer. The absorption recovery, which reflects the time scale for photodissociation followed by recombination and vibrational relaxation of I2− inside the cluster, shows a strong dependence on the composition of the surrounding cluster solvent. The absorption recovery ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
3
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 57 publications
6
71
3
5
Order By: Relevance
“…Vibrational relaxation of the recombined I 2 -in the larger I 2 -(CO 2 ) n clusters was found to be significantly faster (<5 ps) than in I 2 -(Ar) 20 , in agreement with the absorption recovery experiments by Lineberger. 190 However, solvent evaporation was clearly much slower, and comparison to the tandem mass spectrometric data obtained by Lineberger 189 showed that evaporation was incomplete for pump-probe delay times as long as 200 ps. The faster relaxation and slower evaporation times are consistent with the stronger solute-solvent coupling and higher solvent density of states in I 2 -(CO 2 ) n clusters.…”
Section: Photodissociation Recombination and Reaction Dynamics In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrational relaxation of the recombined I 2 -in the larger I 2 -(CO 2 ) n clusters was found to be significantly faster (<5 ps) than in I 2 -(Ar) 20 , in agreement with the absorption recovery experiments by Lineberger. 190 However, solvent evaporation was clearly much slower, and comparison to the tandem mass spectrometric data obtained by Lineberger 189 showed that evaporation was incomplete for pump-probe delay times as long as 200 ps. The faster relaxation and slower evaporation times are consistent with the stronger solute-solvent coupling and higher solvent density of states in I 2 -(CO 2 ) n clusters.…”
Section: Photodissociation Recombination and Reaction Dynamics In Amentioning
confidence: 99%
“…The pioneering work by Lineberger and co-workers [187][188][189][190][191] papers. [198][199][200][201] The maximum sizes in both cases represent complete solvent shells.…”
Section: Photodissociation Recombination and Reaction Dynamics In Amentioning
confidence: 99%
“…In particular, I 2 Ϫ has been studied in a wide variety of environments, including gas phase clusters, [3][4][5][6][7][8][9][10][11][12] liquid solutions, [13][14][15][16][17][18][19][20][21] and gas-surface collisions, [22][23][24][25] and these experiments have stimulated a variety of theoretical studies. These solvated molecular ions differ considerably from their neutral counterparts, since the interaction between the ion and the surrounding solvent, which can be as strong as the chemical bonding forces within the solute, depends sensitively on the solute charge distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The bond angle has been determined by a variety of experimental [31][32][33][34] and theoretical [29,35] methods to be ca. 134 . In a linear geometry, the CO À 2 ion is in a 2 P u state, whose degeneracy is lifted upon deformation and splits into the 2 A 1 ground state of the anion (with the excess electron in the 6a 1 orbital) and a 2 B 1 excited state (with the excess electron in the 2b 1 orbital).…”
Section: Introductionmentioning
confidence: 95%